2008
DOI: 10.1038/nrm2430
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of TNFR1 and CD95 signalling by receptor compartmentalization

Abstract: The death receptors tumour-necrosis factor receptor-1 (TNFR1) and CD95 (also known as FAS and APO-1) transduce signals that promote cell death by apoptosis. However, these receptors are also capable of inducing anti-apoptotic signals through the activation of the transcription factor nuclear factor-kappaB (NF-kappaB) or through activation of the proliferative mitogen-activated protein kinase (MAPK) cascade. Recent findings reveal a role for receptor internalization and endosomal trafficking in selectively tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
220
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(234 citation statements)
references
References 70 publications
8
220
1
5
Order By: Relevance
“…The function of TNF a is ambiguous in various cell types because TNF a is mediated by two receptors with different activation paths [53]. The activation of TNF receptor 1 has been reported to decrease MSC growth factor production [54], generate reactive oxygen species, and induce apoptosis [55] whereas TNF receptor 2 has been demonstrated to enhance MSC growth through the activation of NF-jB [56]. Conversely, it has been shown that fetal and adult MSCs are killed by different pathways; in particular, fetal MSCs are preferably killed via TNF a while the adult MSCs are more sensitive to FasL pathway [57].…”
Section: Discussionmentioning
confidence: 99%
“…The function of TNF a is ambiguous in various cell types because TNF a is mediated by two receptors with different activation paths [53]. The activation of TNF receptor 1 has been reported to decrease MSC growth factor production [54], generate reactive oxygen species, and induce apoptosis [55] whereas TNF receptor 2 has been demonstrated to enhance MSC growth through the activation of NF-jB [56]. Conversely, it has been shown that fetal and adult MSCs are killed by different pathways; in particular, fetal MSCs are preferably killed via TNF a while the adult MSCs are more sensitive to FasL pathway [57].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the past decade it has become apparent that internalization and intracellular trafficking of receptors also can have a stimulatory role in certain signaling pathways. Internalization and compartmentalization of TNFR1 and Fas following ligand binding may have a key role in directing signal transduction (Schutze et al, 2008). Clathrin-mediated endocytosis of TNFR1 and Fas has been shown to be required for apoptosis stimulation, but not for activation of the NF-kB and MAPK pathways.…”
Section: Recent Advances In Understanding Apoptosis Initiationmentioning
confidence: 99%
“…Fas-associated death domain protein (Schu¨tze et al, 2008), which in turn recruits and aggregates several molecules of caspase-8, thereby promoting its autoprocessing and activation. Activation of caspase-8 processes other effector caspase members, including caspase-3 and caspase-7 to initiate a caspase cascade.…”
Section: T-box Transcription Factor 5 In Colon Cancer J Yu Et Almentioning
confidence: 99%